2021
DOI: 10.18553/jmcp.2021.27.10.1403
|View full text |Cite
|
Sign up to set email alerts
|

Association of dyskalemias with short-term health care utilization in patients with advanced CKD

Abstract: BACKGROUND: Patients with advanced chronic kidney disease (CKD) are at high risk for dyskalemias, which may induce arrhythmias that require immediate emergent or hospital care. The association of dyskalemias with short-term hospital/emergency room (ER) visits in advanced CKD is understudied. OBJECTIVE:To assess the association of dyskalemias with short-term hospital/ER visits in an advanced CKD population. METHODS:From among 102,477 US veterans transitioning to dialysis from 2007 to 2015, we identified 21,366 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…High serum uric acid levels are associated with high risk for advanced CKD and CKD progression [ 51 , 52 ], the prevalence of hyperuricemia was 30.9% in advanced CKD; advanced CKD had a 2.4-fold higher OR if a patient had hyperuricemia and 2.4-fold higher if a patient was on allopurinol; similar findings have been reported in other studies [ 23 , 53 ]. Hyperkalemia is common in patients with chronic CKD and its prevalence increases as the eGFR declines [ 54 , 55 ], approximately 8.8% patients with advanced CKD were found to have hyperkalemia; hyperkalemia had a 5.4-fold increased association with advanced CKD; similar findings have been reported in other studies [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 71%
“…High serum uric acid levels are associated with high risk for advanced CKD and CKD progression [ 51 , 52 ], the prevalence of hyperuricemia was 30.9% in advanced CKD; advanced CKD had a 2.4-fold higher OR if a patient had hyperuricemia and 2.4-fold higher if a patient was on allopurinol; similar findings have been reported in other studies [ 23 , 53 ]. Hyperkalemia is common in patients with chronic CKD and its prevalence increases as the eGFR declines [ 54 , 55 ], approximately 8.8% patients with advanced CKD were found to have hyperkalemia; hyperkalemia had a 5.4-fold increased association with advanced CKD; similar findings have been reported in other studies [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 71%
“…Patiromer may provide clinical benefit by allowing patients with advanced CKD to start or remain on RAAS inhibitors, which are recognized as a cornerstone of therapy in patients with CKD due to their beneficial cardiorenal effects. 9 , 10 , 11 , 12 In an exploratory analysis of the OPAL-HK 12-week study, 94% of patients assigned to patiromer remained on RAAS inhibitor or MRA therapy at week 12 versus 44% of placebo patients. 20 The AMBER and DIAMOND trials also demonstrated consistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperkalemia is associated with a higher risk of adverse clinical outcomes, including mortality, cardiovascular events, hospitalizations, and progression to kidney failure with replacement therapy (KFRT). 7 , 9 , 10 , 11 , 12 The association between hyperkalemia and adverse outcomes may be explained by its known cardiac electrophysiologic effects. 13 Severe hyperkalemia predisposes to both cardiac hyperexcitability and depression, either of which can lead to fatal arrhythmias.…”
mentioning
confidence: 99%
“…1,3 Hyperkalemia is associated with a significant healthcare and economic burden. [4][5][6][7] Previous US-based studies have shown that patients who experience hyperkalemia incur substantially higher all-cause healthcare costs than matched controls, with inpatient visits being the main driver of increased cost. 5,7,8 Healthcare resource utilization has also been shown to be significantly higher among patients who experience hyperkalemia than for matched controls.…”
Section: Introductionmentioning
confidence: 99%